Adaptive tracking control of a class of nonlinear systems with unknown dead-zone output: a multi-dimensional Taylor network (MTN)-based approach. Issue 11 (2nd November 2021) - Han, Yu-Qun
ABSTRACT: In this paper, an approximation-based adaptive multi-dimensional Taylor network (MTN) control approach is proposed for a class of nonlinear systems with unknown dead-zone output. Firstly, MTNs are utilised to approximate the unknown nonlinearity of the system. Secondly, the relation of the unknown function f 1 ( x 1 ) and the output y is establish. Thirdly, integrating adaptive control method and MTNs into the backstepping design process, a novel MTN-based adaptive controller is constructed by introducing a Nussbaum function. The proposed control scheme has the advantages of simple structure and small calculation. Finally, two simulation examples are given to illustrate the effectiveness of the method proposed in this paper.